The assessment formative and the Zone of Proximal Development (Research, Society and Development, 2019)
This article aims to present the possible relationships between formative assessment and the Zone of Proximal Development of Vygotsky. As a research method, we have chosen to use speculative research, since the intention is to produce a theoretical text based on other theoretical texts. The Zone of Proximal Development can be considered as the space between the level of real development and the level of potential development. The formative evaluation can be understood as a school process that aims to identify and modify the learning gap of the students, being a way to identify the real development zone and intervene so that the student reaches all its potential development. It is concluded that the formative assessment can be seen as complementary to the concept of Zone of Proximal Development when it comes to student learning.